Hydrophilic enhancement of Polysulfone membrane via Graphene Oxide embedded thin film nanocomposite for Isopropanol dehydration - Mohamad Syafiq, Abdul Wahab; Sunarti, Abd Rahman; Rozaimi, Abu Samah (Elsevier, 2020)
Graphene oxide (GO) was introduced in this study as a hydrophilic enhancer to polyether block amide copolymer (PEBAX) in the form of thin film nanocomposite (TFNC) for hydrophobic based polysulfone (PSF) membrane. The objective is to increase hydrophilic moieties by providing more polar terminal within the TFNC network and by doing so, the film managed to completely reduce IPA traces in the permeate from 0.8 wt % while maintaining a constant flux of 1.2 kg/m2h. SEM, FTIR and water contact angle was used to characterized the produced film. The contact angle was also reduced from 77.5_ to 37.48_, indicating the increment of hydrophilicity of the film. Interestingly, the GO incorporated film could take up to 38.02% of water, proving a possibility for this TFNC to be used in pervaporation.